Mordechaj Chaim Rumkowski – literackie oceny i interpretacje - Polit, Monika (Zagłada Żydów. Studia i Materiały, 2011)
The text attempts to reconstruct Mordechaj Chaim Rumkowski’s image emerging from texts written after the war in different languages. In most cases the authors, though clearly fascinated with Rumkowski, could not or would not strive to get under the layer of what is stereotypical in the perception of the Chief of the Elders of the Jews in the Łódź ghetto.